2018
DOI: 10.3390/nano8070494
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Performance of Nano-Titanium Nitride-Coated Stainless Steel Electrodes in Electro-Fenton Systems

Abstract: The electro-Fenton (EF) process is a type of electrochemical oxidation process; ·OH radicals are generated on the cathode using electricity and decolorize dye wastewaters. Most studies on EF systems in the past have focused on the operating parameters of this process. In recent years, the influence of electrode performance on the EF process has begun to receive more attention. In this study, direct nitridation was used to prepare titanium nitride powders, which were thereafter coated on an SUS304 stainless ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In half a period the targets change their roles. A disc anode (6) inside the chamber is connected through feedthrough (7) to the positive pole of a DC power supply (8) and its negative pole is connected to the grounded chamber. The power supply provides the discharge voltage 300-1200 V at a stabilized current of 1-4 A.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In half a period the targets change their roles. A disc anode (6) inside the chamber is connected through feedthrough (7) to the positive pole of a DC power supply (8) and its negative pole is connected to the grounded chamber. The power supply provides the discharge voltage 300-1200 V at a stabilized current of 1-4 A.…”
Section: Methodsmentioning
confidence: 99%
“…The useful life of tools, machine parts, and other products can be increased due to vacuum arc deposition [1][2][3][4][5] of wear-resistant TiN [6,7] and other coatings with a microhardness of~25 GPa, whose manifold exceeds hardness of the product material. The thickness of wear-resistant coatings synthesized on tools for rough cutting usually does not exceed 5-7 µm.…”
Section: Introductionmentioning
confidence: 99%
“…The same group recently demonstrated the selective laser sintering of the LCO/LLZO composite layer without undesired reaction with metallic substrates (Figure 8). [103] As shown in Figures 8a and b, the XRD analyses revealed that several secondary phase materials, such as LiFeO 2 , LiAl 2 Cr 3 O 8 , and Al 95 Fe 4 Cr, could be produced by the reaction of composite layer and metal elements from SUS substrates during the RTA process [110] . Consequently, the RTA‐treated composite cathode exhibited a completely decomposed LLZO phase.…”
Section: Interfacial Engineering Via Selective Laser Sinteringmentioning
confidence: 96%
“…Vereschaka et al [13] obtained that a nanostructured and multi-layered coated tool's life exceeded by 3 times the tool life of an uncoated tool, and by more than 2 times the tool life of a tool with standard coating. In the study by Wang and Lin [14] investigated the performance of nano-TiN coated stainless steel cathodes and obtained that improving electrode performance in electrochemical wastewater treatments.…”
Section: Introductionmentioning
confidence: 99%